Basis of Plotinus’ critique of Aristotle’s theory of categories - Woszczyk, Agnieszka (Folia Philosophica, 2011)
The paper is devoted to analysis of the critique of Aristotelian theory of categories from Enneads, its main arguments and the relation of Plotinus’ theory of the kinds of sense world (kosmos aistheotos) to Aristotle’s categories. According to Plotinus, Aristotelian notion of categories is not a relevant tool of grasping the being in adequate sense, that is, as noetic being. The main argument is focused on the category of substance. There is a difference between how the problem of the kinds of beings is understood in Enn. VI 1 [42] and in Enn. VI 3 [44]. In the latter a basis for taking into account a modified form of Aristotelian categories as acceptable way of predicating of changeable sensual objects can be pointed out.